Kemandirian Peradilan Agama dalam Perspektif Undang-Undang Peradilan Agama - Sumadi Matrais (Fakultas Hukum Universitas Islam Indonesia, 2008)
It is widely understood that Islamic court in Indonesia is not an independent body of court of justice or judiciary system. This is caused mainly by the lack of legal support. So, it may be concluded that the dependency of religious court in Indonesia is as a sensible consequence of the flaws in the existing legal framework